Effectiveness of Neurostimulation Technologies for the Management of Chronic Pain: A Systematic Review. Issue 2 (16th July 2019) - Hofmeister, Mark; Memedovich, Ally; Brown, Sage; Saini, Manik; Dowsett, Laura E.; Lorenzetti, Diane L.; McCarron, Tamara L.; MacKean, Gail; Clement, Fiona
Abstract : Objectives: To describe the state of the literature for clinical effectiveness of neurostimulation used for the management of chronic pain. Methods: A systematic review of spinal cord stimulation (SCS), peripheral nerve stimulation (PNS), peripheral nerve field stimulation (PNFS), and supraorbital transcutaneous electrical nerve stimulation in patients with cancer and noncancer chronic pain was conducted. MEDLINE, Embase, CINAHL, and the Cochrane CENTRAL Register of Controlled Trials were searched, using terms like "electrical stimulation therapy" and "pain management." Direction of effect, consistency across studies, and strength of evidence for effects of neurostimulation on chronic pain were narratively synthesized. Results: A total of 15 randomized controlled trials (RCTs) examining SCS, 7 RCTs examining PNS/PNFS, and 1 nonrandomized trial examining supraorbital transcutaneous electrical nerve stimulation (TENS) were included. In nine SCS studies, neurostimulation had positive effects on pain. In three studies, neurostimulation did not significantly reduce pain. For PNS/PNFS, five studies found improvements in pain offered by neurostimulation; pain outcomes were not reported in two studies. In the TENS study, neurostimulation reduced headaches per month and medication consumption. Overall, 21 studies were of low or unclear risk of bias, 4 were high risk of bias, and the TENS study was not appropriate for assessment using the Cochrane Risk of Bias tool. Conclusions: A robust body of evidence examining SCS and PNS was identified. Only one study for PNFS and TENS was identified; both reported pain reductions. Generally, neurostimulation improved pain control. Future studies should examine the effectiveness of neurostimulation offered early in the trajectory of chronic pain.